Efficient cement grinding aid and preparation method thereof
By using polyol compounds, organic acid salts, surfactants and other components in cement aids, combined with ultrasonic stirring and microporous spherical particles, the problem of rapid coagulation and agglomeration caused by cement aids is solved, and the problem of excessive coagulation and agglomeration caused by cement aids is achieved. High-efficiency grinding and stability improvement of cement.
Patent Information
- Application Number
- CN202411602024.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cement agitators cause the cement to set too fast during construction, the cement strength and corrosion resistance after hardening are insufficient, and it is prone to agglomeration during long-term storage, resulting in unsatisfactory stability.
Using a high-efficiency cement aid, including polyol compounds, organic acids, surfactants, enhancers, defoamers, nanosilica, calcium lignin sulfonate and modified starch, stirring and micro-split by ultrasonic wave The design of pore spherical particles works synergistically to improve grinding efficiency and dispersion of cement, and prevent agglomeration.
It significantly improves the grinding efficiency and strength of cement, extends the settling time, improves the cement's ease, durability and corrosion resistance, ensures that cement can maintain a high strength growth in the early and later stages, and optimizes Particle grading and structural density.
Smart Images

Figure CN119143423A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement grinding aids, and in particular to a high-efficiency cement grinding aid and a preparation method thereof. Background Art
[0002] In the cement production process, the grinding of cement raw materials and clinker is indispensable, but this process consumes a lot of energy and the energy utilization rate is not high. The reason is that when cement particles are refined, they have a tendency to agglomerate automatically due to their large surface energy. To solve this problem, cement grinding aids are generally added to improve grinding efficiency and prevent agglomeration.
[0003] For example, the patent document CN109503018B discloses a cement grinding aid, which mainly contains nitrilotriacetic acid and ethylene glycol reactants, isooctyl phosphate, amine compounds and surfactants as main components, and can promote the dispersion of cement particles and prevent agglomeration. However, in actual use, especially for some projects with a long construction time, cement coagulates too quickly, and the strength and corrosion resistance of hardened cement are average. Moreover, cement with a long construction period may re-agglomerate during storage, and its stability performance is not ideal. In view of this, the present application proposes a high-efficiency cement grinding aid and a preparation method thereof. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-efficiency cement grinding aid and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A high-efficiency cement grinding aid comprises the following raw materials in percentage by weight: Polyol compounds 15%-30%, organic acid salts 10%-15%, surfactants 12%-20%, enhancers 10%-15%, defoamers 0.3%-5%, nano-silicon dioxide 3%-5%, calcium lignin sulfonate 5%-8%, sodium tripolyphosphate 2%-4% and modified starch 1%-3%.
[0006] Preferably, the polyol compound is propylene glycol and ethylene glycol in a mass ratio of 2:1, and the organic acid salt is a composite salt of sodium citrate and sodium tartrate in a mass ratio of 3:1.
[0007] Preferably, the surfactant is sodium dodecylbenzene sulfonate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:3, the enhancer is triethanolamine and diethanol monoisopropanolamine mixed in a mass ratio of 1:1.5, and the defoamer is polydimethylsiloxane.
[0008] Preferably, the particle size of the nano-silicon dioxide is in the range of 30 to 50 nm.
[0009] The above-mentioned method for preparing a high-efficiency cement grinding aid comprises the following preparation steps: S1, raw material pretreatment, propylene glycol, ethylene glycol, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, polydimethylsiloxane are sprayed into the low-temperature vacuum pretreatment chamber through ultra-fine atomization nozzles to form tiny droplets and quickly atomize and cool; S2, mixing and dispersing, putting the atomized raw material obtained in step S1 into an ultrasonic reactor, stirring at a speed of 2000-3000 r / min for 5-10 minutes at an environment of 20-30°C, and then stirring at a speed of 300-500 r / min for 10-15 minutes; S3, preparing solid raw material spherical particles, sodium citrate, sodium tartrate, triethanolamine, diethanol monoisopropanolamine, calcium lignin sulfonate, and sodium tripolyphosphate are pre-mixed, and the mixed solid raw materials are mixed with a small amount of sodium alginate solution to prepare spherical particles with micropores having a diameter of 3-6 mm; S4, dissolving, putting the spherical particles obtained in step S3 into the bottom of the ultrasonic reactor, and starting the ultrasonic generator at the bottom of the reactor at the same time, setting the frequency to 30-50kHz, when all the solid raw materials are added, raising the temperature in the reactor to 40-50°C at a rate of 1-2°C / min, and maintaining this temperature at a speed of 500-800r / min, and continuing to stir for 20-30 minutes, after the atomized solution enters the micropores of the spherical particles, it can be fully mixed and contacted with the solid raw materials, and under stirring and ultrasonic cavitation, the spherical particles are gradually and evenly dissolved and dispersed in the atomized solution; S5, adding nano-silicon dioxide and modified starch, after dissolution is completed, slowly adding nano-silicon dioxide into the reaction system, and continue stirring and ultrasonic treatment for 10-15 minutes, then adjusting the modified starch into a paste with a small amount of water, and continue stirring for 10-15 minutes; S6, post-processing, filtering the grinding aid obtained in step S5 through a 300-500 mesh filter to remove undissolved impurities and large particles, and then fine filtering through a 50-100 mesh filter to obtain a pure grinding aid product, and finally packaging.
[0010] Preferably, in step S1, the setting parameters of the low-temperature hollow pretreatment chamber are a temperature of -10°C to -5°C and a vacuum degree of 0.05-0.1 MPa.
[0011] Preferably, the method for forming micropores of the spherical particles in step S3 is: during the drying and solidification process of the spherical particles, nitrogen is blown into the interior of the spherical particles to form a micropore structure inside the spherical particles.
[0012] The present invention has the following beneficial effects: 1. The cement grinding aid of the present invention significantly improves the grinding efficiency of cement through the synergistic effect of multiple components. During the grinding process, it can effectively reduce the friction and agglomeration between cement particles, make cement particles more refined, optimize the particle grading, thereby increasing the specific surface area of cement. The reasonable compounding of reinforcing agents and the reaction of nano-silica with cement hydration products enable cement to maintain a high strength growth in both the early and late stages, improve the quality and applicability of cement, and improve the comprehensive properties of cement such as workability, durability, and corrosion resistance through ingredients such as lignin sulfonate, sodium tripolyphosphate, and modified starch; 2. In the preparation process, the spherical particles made of solid raw materials and sodium alginate are stirred and ultrasonically treated, and their randomness of movement increases, so that they come into contact with the liquid raw materials more fully and evenly, effectively avoiding the problems of raw material agglomeration and local uneven concentration, and improving the mixing effect; 3. The micropores inside the spherical particles are conducive to the slow release of raw materials, so that they can continuously provide reactive substances during the reaction process. Combined with stirring and ultrasonic vibration, it accelerates chemical reactions and physical mixing and shortens the preparation time. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The period diagram required for complete release of the raw materials inside the solid particle spheres with micropores of different inner diameters in the present invention; Figure 2 It is a curve diagram showing the growth of specific surface area with preparation time during the preparation process of each embodiment and comparative example of the present invention; Figure 3 The compressive strength growth curve of cement prepared in each embodiment and comparative example of the present invention within 28 days of the experiment; Figure 4 The flexural strength growth curve of cement prepared in each embodiment and comparative example of the present invention within 28 days of the experiment; Figure 5 This is a product diagram of the cement grinding aid prepared by the present invention. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0015] A high-efficiency cement grinding aid comprises the following raw materials in percentage by weight: Polyol compounds 15% to 30%, organic acid salts 10% to 15%, surfactants 12% to 20%, enhancers 10% to 15%, defoamers 0.3% to 5%, nano-silicon dioxide 3% to 5%, calcium lignin sulfonate 5% to 8%, sodium tripolyphosphate 2% to 4% and modified starch 1% to 3%. Specifically, the polyol compounds are propylene glycol and ethylene glycol in a mass ratio of 2:1, and the organic acid salt is a composite salt of sodium citrate and sodium tartrate in a mass ratio of 3:1. The surfactant is sodium dodecylbenzene sulfonate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:3, the enhancer is triethanolamine and diethanol monoisopropanolamine mixed in a mass ratio of 1:1.5, and the defoamer is polydimethylsiloxane. The particle size of nano-silicon dioxide is selected in the range of 30 to 50nm.
[0016] Specifically, by adding a certain amount of calcium lignin sulfonate, the dispersion effect of cement particles can be improved and the agglomeration of particles can be prevented. In the cement grinding process, the fluidity of the material can be effectively improved, making the grinding more uniform and efficient. At the same time, it also has a retarding effect, which can adjust the setting time of cement, improve the workability of cement, and prevent cement from setting too quickly. By adding a certain amount of sodium tripolyphosphate, phosphate can form a stable complex with metal ions in cement, inhibit the agglomeration of cement particles, and significantly improve the grinding efficiency during the grinding process. Moreover, phosphates such as sodium tripolyphosphate can also play a retarding and reinforcing role in the cement hardening process, which helps to improve the durability of cement, improve the later strength and corrosion resistance of cement. By adding a certain amount of nano-silicon dioxide, its tiny particle size can fill the tiny gaps between cement particles, optimize the particle packing density, make the cement structure more compact, and thus improve the strength and durability of cement. In the cement hydration process, nano-silicon dioxide can react with hydration products to generate more beneficial products such as calcium silicate gel, further enhancing the structural strength of cement.
[0017] The above-mentioned method for preparing a high-efficiency cement grinding aid comprises the following preparation steps: S1, raw material pretreatment, propylene glycol, ethylene glycol, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, polydimethylsiloxane are sprayed into the low-temperature vacuum pretreatment chamber through ultra-fine atomizing nozzles to form tiny droplets and quickly atomize and cool; the setting parameters of the low-temperature hollow pretreatment chamber are temperature -10°C to -5°C, vacuum degree 0.05-0.1MPa; S2, mixing and dispersing, putting the atomized raw material obtained in step S1 into an ultrasonic reactor, stirring at a speed of 2000-3000 r / min for 5-10 minutes at an environment of 20-30°C, and then stirring at a speed of 300-500 r / min for 10-15 minutes; S3. Prepare spherical particles of solid raw materials. Mix sodium citrate, sodium tartrate, triethanolamine, diethanol monoisopropanolamine, calcium lignin sulfonate and sodium tripolyphosphate in advance, mix the mixed solid raw materials with a small amount of sodium alginate solution, and prepare spherical particles with micropores of 3-6 mm in diameter; the micropores of the spherical particles are formed by blowing nitrogen into the interior of the spherical particles during the drying and curing process of the spherical particles to form a microporous structure inside the spherical particles.
[0018] S4, dissolving, putting the spherical particles obtained in step S3 into the bottom of the ultrasonic reactor, and starting the ultrasonic generator at the bottom of the reactor at the same time, setting the frequency to 30-50kHz, when all the solid raw materials are added, raising the temperature in the reactor to 40-50°C at a rate of 1-2°C / min, and maintaining this temperature at a speed of 500-800r / min, and continuing to stir for 20-30 minutes, after the atomized solution enters the micropores of the spherical particles, it can be fully mixed and contacted with the solid raw materials, and under stirring and ultrasonic cavitation, the spherical particles are gradually and evenly dissolved and dispersed in the atomized solution; The micropores inside the spherical particles are conducive to the slow release of raw materials, allowing them to continuously provide reactive substances during the reaction process. Combined with stirring and ultrasonic vibration, the chemical reaction and physical mixing are accelerated, and the preparation time is shortened. Under the action of stirring and ultrasound, the spherical particles made of solid raw materials and sodium alginate have increased randomness of movement, and the contact with the liquid raw materials is more sufficient and uniform, which effectively avoids the problems of raw material agglomeration and local uneven concentration and improves the mixing effect.
[0019] In addition, the cavitation effect of ultrasound is used to accelerate the dissolution and dispersion of solid raw materials in liquid raw materials. The cavitation effect of ultrasound can produce an instantaneous high temperature and high pressure environment in the liquid, making it easier for the molecules on the surface of the solid raw materials to detach and enter the solution, and can also further break up the possible tiny agglomerates. When all the solid raw materials are added, the temperature in the reactor is raised to 40-50°C at a rate of 1-2°C / minute to allow the organic acid salt and enhancer to fully dissolve and react with other raw materials. Accurate temperature control and appropriate stirring speed help to increase the reaction rate and promote a more complete chemical reaction between the raw materials, thereby improving the quality and performance of the product.
[0020] S5, adding nano-silicon dioxide and modified starch, after dissolution is completed, slowly adding nano-silicon dioxide into the reaction system, and continue stirring and ultrasonic treatment for 10-15 minutes, then adjusting the modified starch into a paste with a small amount of water, and continue stirring for 10-15 minutes; S6, post-processing, filtering the grinding aid obtained in step S5 through a 300-500 mesh filter to remove undissolved impurities and large particles, and then fine filtering through a 50-100 mesh filter to obtain a pure grinding aid product, and finally packaging.
[0021] Finally, the grinding aid and the product obtained by the above process steps are placed in a container, as shown in the following example. Figure 5 shown.
[0022] Example 1: Weigh 12g of propylene glycol, 6g of ethylene glycol, 9g of sodium citrate, 3g of sodium tartrate, 4g of sodium dodecylbenzene sulfonate, 12g of fatty alcohol polyoxyethylene ether, 5g of triethanolamine, 7.5g of diethanol monoisopropanolamine, 0.4g of polydimethylsiloxane, 4g of nano-silicon dioxide, 6g of calcium lignin sulfonate, 3g of sodium tripolyphosphate, and 2g of modified starch.
[0023] Example 2: Weigh 8g of propylene glycol, 4g of ethylene glycol, 10g of sodium citrate, 3.3g of sodium tartrate, 5g of sodium dodecylbenzene sulfonate, 15g of fatty alcohol polyoxyethylene ether, 6g of triethanolamine, 9g of diethanol monoisopropanolamine, 0.3g of polydimethylsiloxane, 5g of nano-silicon dioxide, 5g of calcium lignin sulfonate, 2.5g of sodium tripolyphosphate, and 1.5g of modified starch. (Reduce 25% of polyol compounds).
[0024] Example 3: Weigh 15g of propylene glycol, 7.5g of ethylene glycol, 12g of sodium citrate, 4g of sodium tartrate, 6g of sodium dodecylbenzene sulfonate, 9g of fatty alcohol polyoxyethylene ether, 4g of triethanolamine, 6g of diethanol monoisopropanolamine, 0.5g of polydimethylsiloxane, 3g of nano-silicon dioxide, 8g of calcium lignin sulfonate, 4g of sodium tripolyphosphate, and 3g of modified starch (change the distribution ratio of the two groups of surfactants to 1:1).
[0025] Example 4: Weigh 13g of propylene glycol, 6.5g of ethylene glycol, 11g of sodium citrate, 3.7g of sodium tartrate, 4.5g of sodium dodecylbenzene sulfonate, 13.5g of fatty alcohol polyoxyethylene ether, 5.5g of triethanolamine, 8.3g of diethanol monoisopropanolamine, 0.45g of polydimethylsiloxane, 2g of nano-silicon dioxide, 7g of calcium lignin sulfonate, 3.5g of sodium tripolyphosphate, and 1g of modified starch (reducing nano-silicon dioxide by 50% and reducing modified starch by 50%).
[0026] The raw materials of the above-mentioned embodiments are operated according to the established process preparation steps: ensure sufficient stirring when mixing the liquid raw materials, pay attention to observing the movement and reaction of the solid raw material spherical particles in the reactor after adding them, and adjust the stirring and ultrasonic device parameters in time. When adding nano silicon dioxide and modified starch, ensure that they are evenly dispersed. After the reaction is completed, select a filter screen with appropriate precision for filtering according to the product quality requirements, and finally obtain the cement grinding aid product produced by each embodiment.
[0027] Example 5: Weigh the same raw materials as those in Example 1, and use traditional technology to prepare grinding aids. Do not perform the special spherical particle preparation and mixing reaction process of steps S2-S4. Simply mix the raw materials and finally filter them to obtain cement grinding aids.
[0028] The grinding aids prepared in Examples 1 to 5 and the grinding aids in the comparative example were respectively applied to cement grinding experiments, and the operations were performed according to the same grinding process parameters.
[0029] The effects of the grinding aids were compared by testing cement specific surface area, 3-day and 28-day compressive strength, setting time, 3-day and 28-day flexural strength, etc. Comparative Example 1 used cement grinding aids produced using the background technology of this article, and Comparative Example 2 used cement grinding aids commonly used in the market.
[0030] It should be noted that the main components of the cement grinding aid products commonly used in the market include triethanolamine, ethylene glycol, molasses, etc. The specific experimental operation is as follows: uniformly mix with cement raw materials (cement raw material mix ratio: clinker 65wt%, gypsum 5wt%, slag 20wt%, steel slag 10wt%) at a uniform dosage of 0.015%, and grind in the same standard test mill (Model SM-500 Ф500mm standard test mill produced by Wuxi Jianyi Instrument Machinery Co., Ltd.) for 30 minutes to obtain cement. The performance test parameters of each group of embodiments and comparative examples are as follows:
[0031] In summary, the water grinding aid prepared by the present invention has obvious advantages in performance indicators such as specific surface area, setting time, and fluidity compared with the common cement grinding aids on the market and the cement grinding aids submitted in the background technology of this article. For example, the cement fluidity in Example 1 reaches 260 mm, which is significantly improved compared with 230 mm in Comparative Example 1 (prepared by traditional method). This is due to the synergistic effect of various components in the grinding aid of the present invention, such as the dispersion and retarding effect of lignin sulfonate, the filling and ball effect of nano-silica, etc., which together improve the rheological properties of the cement slurry and improve its fluidity.
[0032] Furthermore, the grinding aids produced by each example group and the comparative example group were used to prepare cement, and the growth change of the specific surface area of each group of cement during the preparation process with the preparation time was recorded to prepare a comparative curve graph, as shown in the following figure: Figure 2 The specific surface area of Example 1, Example 2, Example 3 and Example 4 increased rapidly in the early stage of the preparation process (0-15min), mainly due to the following reasons: Examples 1 to 4 were prepared using the process steps proposed by the present invention, and the raw material pretreatment and mixing and dispersion effects were good; In addition, the synergy between polyol compounds and surfactants can accelerate particle refinement and promote the growth of specific surface area. Under the action of the defoaming agent stabilization system, the foam generated during the mixing process can be eliminated in time to prevent the foam from entraining air to form large pores or affecting the uniformity of raw material mixing, thereby ensuring the stability of the system, helping other components to play a better role, and indirectly promoting the rapid growth of specific surface area.
[0033] In the middle and late stages (25-45min), the growth of specific surface area is slow, mainly reaching the equilibrium of dissolution reaction. At this time, the hydration reaction of cement becomes dominant, and the filling of the voids between particles and the optimization of the structure of the generated hydration products gradually reach a certain level. The effect of improving the specific surface area is no longer significantly increased. At the same time, the particle structure tends to stabilize, limiting the substantial growth of the specific surface area.
[0034] In Example 5, the surface area of the samples was not prepared by the process provided by the present invention. The surface area increased very slowly in the early and middle stages, and there was a downward trend in the middle and late stages (about 35 minutes), and finally reached a lower value (380m 2 / kg), mainly due to the low reaction rate in the early stage, the difficulty in dissolving solid raw materials, the agglomeration of particles and the deterioration of structure. In the conventional preparation process, due to the lack of effective dispersion and stabilization measures (such as calcium lignin sulfonate, sodium tripolyphosphate and other components in the present invention to cooperate with other components to prevent particle agglomeration), as the reaction proceeds, the agglomeration of particles gradually intensifies. The particles aggregate with each other to form larger agglomerates, so that the originally refined particles recombine, and the specific surface area decreases instead of increases. After the slow reaction in the early and middle stages, there are not many unreacted raw materials left in the system in the later stage. Although the reaction is still continuing, due to the limited amount of reactable substances, the newly generated products have less and less effect on improving the specific surface area. For example, the cement hydration reaction gradually becomes flat in the later stage due to the decrease in the concentration of reactants, and the amount of hydration products generated is limited, and the contribution to the increase in specific surface area is weak.
[0035] Refer to Figure 2 , the specific surface area of the two samples increased slowly in the early stage (0-15min), rapidly in the middle stage (15-25min), and slowly in the later stage, and finally rose to 390m 2 / kg, 375m 2 / kg, because without the specific pretreatment (such as atomization cooling, etc.) and mixing process (such as high-speed stirring followed by low-speed stirring) in the present invention, it is difficult to quickly achieve uniform mixing, the interaction between particles cannot be effectively destroyed, and the specific surface area is difficult to increase rapidly. At the same time, there is a lack of synergistic promotion mechanism. In the early mixing process, there is no synergistic effect of polyol compounds and surfactants in the present invention to improve material fluidity and promote particle dispersion, and there is no suitable combination to quickly stimulate reaction activity, resulting in slow particle refinement and hindered growth of specific surface area. In the middle period, some ingredients in its formula (such as amine compounds, etc.) may begin to exert strong reaction activity. These ingredients begin to promote the chemical reaction of cement particles at a certain temperature and mixing conditions. In addition, as the grinding proceeds, the system temperature rises to a certain range, which accelerates the reaction rate of some ingredients, promotes further crushing and structural adjustment of particles, and thus the specific surface area grows rapidly. However, this growth may be relatively disordered because of the lack of a good dispersion and synergistic basis in the early stage.
[0036] In addition, the grinding aids produced by each example group and the comparative example group were used to prepare cement, and the changes in the compressive strength and flexural strength of each group of cement within 28 days of the experiment were recorded during the entire preparation process to prepare a comparison curve, as shown in the following figure. Figure 3 and Figure 4 As shown, Figure 3 This is the curve of compressive strength growth during the 28-day experiment. Figure 4 This is a curve of the flexural strength growth during the 28-day experiment.
[0037] For the compressive strength and flexural strength of cement, it is generally indicated by the test values at 3 days and 28 days. Figure 3 and Figure 4 The water grinding aid prepared by the present invention has obvious advantages in the indicators of 3-day and 28-day compressive strength compared with the common cement grinding aids on the market and the cement grinding aids submitted in the background technology of this article. For Example 2 in which the content of polyol compounds is reduced, when the content of polyol compounds is reduced by 25%, the 3-day compressive strength, flexural strength, 28-day compressive strength and flexural strength are all lower than those of Example 1. This indicates that in this system, the synergistic effect formed by polyol compounds with other components at the standard content is destroyed, and the reduction of their content affects the effect of improving material fluidity and promoting particle dispersion together with surfactants, thereby affecting the strength.
[0038] Due to the changes in polyol compounds, the synergistic effect with the reinforcing agent is weakened, resulting in insufficient stimulation of hydration activity, which affects the early strength development; at the same time, the synergistic effect with other components such as organic acid salts, calcium lignin sulfonate, etc. in particle dispersion and stabilization system is also disturbed, and the overall performance is reduced, indicating that the synergy between the components is interrelated and influential, and the change of one component will break the original synergistic balance.
[0039] For the third embodiment in which the surfactant is changed, after the surfactant ratio is changed to 1:1, the 3-day compressive strength, flexural strength, 28-day compressive strength, and flexural strength are all lower than those in the first embodiment, indicating that the synergistic effect of the surfactant with other components at a specific ratio has changed. The effect of synergizing with polyol compounds to improve fluidity and particle dispersion is affected, resulting in the specific surface area and strength development being inferior to the standard formula, indicating that the 1:3 ratio in the first embodiment can better cooperate with polyol compounds and other components to achieve a better performance improvement effect.
[0040] The change in the proportion of surfactants also affects its synergistic effect with enhancers, defoamers, etc. in the slurry working performance and hydration reaction process. The cement fluidity becomes 240mm, the initial setting time is 112min, and the final setting time is 172min. These changes indicate that the synergistic relationship between the components is complex, and the adjustment of one component will affect the performance of the entire system.
[0041] For Example 4 in which nano-silicon dioxide and modified starch are reduced, after the nano-silicon dioxide is reduced by 50% and the modified starch is reduced by 50%, the 3-day compressive strength, flexural strength, 28-day compressive strength and flexural strength are also lower than those in Example 1, indicating that the role of nano-silicon dioxide in synergizing with other components to fill voids and optimize the structure is weakened, affecting the strength and density; the reduction of modified starch affects the slurry stability and water retention, and indirectly affects the strength development. The reduction of both destroys the synergistic balance with other components and reduces the comprehensive performance of cement.
[0042] The reduction of these two components also affected the synergy with calcium lignin sulfonate, sodium tripolyphosphate, etc. in particle dispersion and setting time regulation. The initial setting time was extended to 120 min, the final setting time was extended to 185 min, and the cement fluidity was reduced to 225 mm, indicating that the synergistic effects of each component are interdependent. The absence or reduction of some components will lead to an imbalance in the overall synergistic system and affect many aspects of cement performance.
[0043] In addition, refer to Figure 3 and Figure 4, the 3-day compressive strength and flexural strength of Example 5, Comparative Example 1, and Comparative Example 2, and the 28-day compressive strength and flexural strength are lower than those of Example 1. For Example 5: There is a lack of special mixing process. Example 5 does not adopt the special spherical particle preparation and mixing reaction process of steps S2-S4 of the present invention, and only simply mixes the raw materials. In the simple mixing process, the raw materials cannot be fully contacted and evenly dispersed as under the special process. For example, without ultrasonic vibration and a specific stirring sequence in an ultrasonic reactor, the mixing effect between the solid raw materials and the liquid raw materials is poor, which may cause some raw materials to agglomerate, and the role of each component cannot be fully exerted, which affects the hydration reaction and structure formation of the cement, thereby reducing the strength.
[0044] Impact of lack of microporous structure: Without preparing spherical particles with micropores, it is impossible to use the microporous structure to achieve slow release and continuous reaction of raw materials. During the cement hydration process, the raw materials cannot continue to effectively participate in the reaction, resulting in insufficient or uneven generation of hydration products, affecting the structural density and strength development of cement paste. For example, key ingredients such as reinforcing agents cannot be continuously supplied, affecting the progress of the hydration reaction and the quality of the product, making the compressive and flexural strengths at 3 days and 28 days lower than those in Example 1.
[0045] As for comparative example 1 and comparative example 2, there is a lack of optimized combination of multiple components in the present invention. Although triethanolamine and other ingredients have certain grinding aids and promote hydration, the overall formula is not as comprehensive as the present invention in improving cement strength. For example, there are no ingredients such as organic acid salts and modified starch similar to those in the present invention to synergistically improve cement performance, resulting in limited development of cement structure and performance, and the strength is lower than that of Example 1. When combined with the cement in this experiment, it cannot fully play its role, and it is impossible to improve the strength by the synergy of process and ingredients like the present invention. For example, in the grinding and mixing process of this experiment, it cannot effectively promote the optimization of particle dispersion and hydration reaction, which affects the strength development of cement stone, making the 3-day and 28-day strength indicators all relatively low.
[0046] Further, a group of Example 6 is added: In this example, the raw material composition is the same as that of Example 1, and in the preparation process steps, when preparing spherical particles, several groups of solid particle balls with different inner diameter micropores are made, and the other process steps are exactly the same, and the cycle required for the complete release of the internal raw materials of the solid particle balls with different inner diameter micropores under the same process conditions is recorded. The results are shown in Figure 1 .
[0047] like Figure 1As shown in the figure, as the inner diameter of the micropore increases, the period required for the complete release of the raw materials inside it gradually shortens, and when the inner diameter of the micropore exceeds 3.5mm, the period begins to lengthen again. Specifically, when the inner diameter of the micropore is less than 3.5mm, as the inner diameter of the micropore gradually increases from a smaller value, the diffusion path of the raw material in the micropore becomes relatively shorter. For example, when the inner diameter increases from 2mm to 3mm, the distance for the raw material molecules to reach the surface of the micropore and be released into the surrounding solution is reduced, which allows the raw material to diffuse out faster under the same stirring and ultrasonic vibration conditions, thereby shortening the period required for complete release.
[0048] In addition, the contact area increases: a larger micropore inner diameter means a larger inner surface area, and the contact area between the raw material and the micropore wall and the surrounding solution increases. Under stirring and ultrasound, more raw material molecules can participate in the interaction with the solution at the same time, accelerating the rate of dissolution and release, just like opening more channels for the raw material to flow out faster, shortening the release cycle.
[0049] When the inner diameter of the micropore exceeds 3.5 mm, the complete release period is prolonged, mainly due to the following two factors: 1. Agglomeration effect: When the inner diameter of the micropores is too large, exceeding 3.5mm, the raw materials may aggregate to a certain extent inside the spherical particles due to the large space. In the process of preparing spherical particles, the original uniform dispersion of the raw materials may be destroyed, and the larger space makes it easier for some raw materials to aggregate together during the drying and curing process. In the release process, these agglomerates need to be depolymerized before they can be completely released, which increases the difficulty and time of release and leads to a longer cycle.
[0050] 2. Uneven solution penetration: Although large inner diameter micropores may allow the solution to enter faster initially, as the reaction proceeds, the solution may become unevenly permeated in the overly large micropores. The solution may flow preferentially along certain channels, while the raw materials in some areas cannot be infiltrated and dissolved by the solution in time, resulting in incomplete and uneven release of the raw materials, thereby prolonging the overall release cycle. Just like water flowing through a large and irregular pipe, there may be a situation where the water flow is large in some places and dry in other places, affecting the effective release of the raw materials.
[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high-efficiency cement grinding aid, characterized in that: The following raw materials are included in weight percentage: Polyol compounds 15%-30%, organic acid salts 10%-15%, surfactants 12%-20%, enhancers 10%-15%, defoamers 0.3%-5%, nano-silicon dioxide 3%-5%, calcium lignin sulfonate 5%-8%, sodium tripolyphosphate 2%-4% and modified starch 1%-3%.
2. A high-efficiency cement grinding aid according to claim 1, characterized in that: The polyol compound is propylene glycol and ethylene glycol in a mass ratio of 2:1, and the organic acid salt is a composite salt of sodium citrate and sodium tartrate in a mass ratio of 3:
1.
3. A high-efficiency cement grinding aid according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate and fatty alcohol polyoxyethylene ether mixed in a mass ratio of 1:3, the enhancer is triethanolamine and diethanol monoisopropanolamine mixed in a mass ratio of 1:1.5, and the defoamer is polydimethylsiloxane.
4. A high-efficiency cement grinding aid according to claim 1, characterized in that: The particle size of the nano silicon dioxide is selected in the range of 30 to 50 nm.
5. The method for preparing a high-efficiency cement grinding aid according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: S1, raw material pretreatment, propylene glycol, ethylene glycol, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, polydimethylsiloxane are sprayed into the low-temperature vacuum pretreatment chamber through ultra-fine atomization nozzles to form tiny droplets and quickly atomize and cool; S2, mixing and dispersing, putting the atomized raw material obtained in step S1 into an ultrasonic reactor, stirring at a speed of 2000-3000 r / min for 5-10 minutes at an environment of 20-30°C, and then stirring at a speed of 300-500 r / min for 10-15 minutes; S3, preparing solid raw material spherical particles, sodium citrate, sodium tartrate, triethanolamine, diethanol monoisopropanolamine, calcium lignin sulfonate, and sodium tripolyphosphate are pre-mixed, and the mixed solid raw materials are mixed with a small amount of sodium alginate solution to prepare spherical particles with micropores having a diameter of 3-6 mm; S4, dissolving, putting the spherical particles obtained in step S3 into the bottom of the ultrasonic reactor, and starting the ultrasonic generator at the bottom of the reactor at the same time, setting the frequency to 30-50kHz, when all the solid raw materials are added, raising the temperature in the reactor to 40-50°C at a rate of 1-2°C / min, and maintaining this temperature at a speed of 500-800r / min, and continuing to stir for 20-30 minutes, after the atomized solution enters the micropores of the spherical particles, it can be fully mixed and contacted with the solid raw materials, and under stirring and ultrasonic cavitation, the spherical particles are gradually and evenly dissolved and dispersed in the atomized solution; S5, adding nano-silicon dioxide and modified starch, after dissolution is completed, slowly adding nano-silicon dioxide into the reaction system, and continue stirring and ultrasonic treatment for 10-15 minutes, then adjusting the modified starch into a paste with a small amount of water, and continue stirring for 10-15 minutes; S6, post-processing, filtering the grinding aid obtained in step S5 through a 300-500 mesh filter to remove undissolved impurities and large particles, and then fine filtering through a 50-100 mesh filter to obtain a pure grinding aid product, and finally packaging.
6. The method for preparing a high-efficiency cement grinding aid according to claim 5, characterized in that: In the step S1, the setting parameters of the low-temperature hollow pretreatment chamber are a temperature of -10°C to -5°C and a vacuum degree of 0.05-0.1 MPa.
7. The method for preparing a high-efficiency cement grinding aid according to claim 5, characterized in that: The method for forming micropores of the spherical particles in step S3 is: during the drying and solidification process of the spherical particles, nitrogen is blown into the interior of the spherical particles to form a micropore structure inside the spherical particles.
Citation Information
Patent Citations
A cement grinding aid
CN109503018B
Lignocellulose type cement grinding aid and preparation method thereof
CN109320129A
Saline-alkali tolerant slow-release water-absorbent resin and application thereof
CN113105578A
Grinding aid for improving early strength of cement and method for improving early strength
CN115231844A
Modified alcohol amine efficient cement grinding aid and preparation method thereof
CN115819005A
Cited By
Enhanced efficient cement activation grinding aid and preparation method thereof
CN119977397A
